Draft Annual Plan 2011-12 (Volume - I) (Write-up) Haryana State - Planning Commission (Planning Commission, 2011)
The State economy recorded the excellent growth during the year 2007-08. The Gross State Domestic Product (GSDP) of Haryana at constant (1999-2000) prices was ₹94268.40 crore and 103244.09 crore in 2006-07 and 2007-08, respectively recording the growth of 9.5 percent during the year 2007-08. However, the growth rate slowed down during the years 2008-09 and 2009-10. The GSDP at constant (1999-2000) prices has been estimated at ₹111420.13 crore and ₹120407.14 crore during the years 2008-09 and 2009-10, respectively witnessing the annual growth of 7 9 and 8.1 percent during the years 2008-09 and 2009-10, respectively. It shows that the growth rate of state economy remained about 8 percent or more during the years 2007-08 to 2009-10.
Planning Department, Government of Haryana